The Determinants of Commercial Banks’ Liquidity in Algeria: A Panel Data Analysis 2010-2020 - Youssef RAKHROUR; Billel BENILLES (Journal of North African Economies, 2025)
This paper aims to identify the determinants of liquidity of Algerian banks. By means of a panel data analysis, we used data from all commercial banks operating in Algeria (20 banks: 6 public and 14 private) during the period 2010-2020. We tested the impact of some internal characteristics of these banks and some macroeconomic indicators on the liquidity of Algerian banks, we used as a proxy of liquidity the ratio: liquid assets/total assets. The results of this study indicate that capital adequacy, deposits, GDP growth rate and lending rate affect positively and significantly the liquidity of Algerian banks, while credits, size, asset quality and operational efficiency influence negatively Banks’ liquidity. For ownership bank, the results show that private banks have higher liquidity ratios than public banks. Regarding the oil shock and the profitability of the bank, they have insignificant impact on the liquidity.